2012
DOI: 10.1002/we.541
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Beddoes–Leishman dynamic stall model for horizontal axis wind turbines using MEXICO data

Abstract: The aim of this study is to assess the load predicting capability of a classical BeddoesLeishman dynamic stall model in a horizontal axis wind turbine (HAWT) environment, in the presence of yaw-misalignment. The dynamic stall model was tailored to the HAWT environment, and validated against unsteady thick airfoil data. Subsequently, the dynamic stall model was implemented in a blade element-momentum (BEM) code for yawed flow, and the results were compared with aerodynamic measurements obtained in the MEXICO (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Pereira et al [10] have proven that it is unrealistic to disregard the leading-edge separation, because the wind turbine airfoils are thick. The main features and formulae of the B-L dynamic stall model may be summarized as follows.…”
Section: Beddoes-leishman Semi-empirical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Pereira et al [10] have proven that it is unrealistic to disregard the leading-edge separation, because the wind turbine airfoils are thick. The main features and formulae of the B-L dynamic stall model may be summarized as follows.…”
Section: Beddoes-leishman Semi-empirical Modelmentioning
confidence: 99%
“…Finally, the nonlinear pitching moment coefficient is obtained by Equation (14), and a rotational increment is added as well. According to the recommendations of Pereira et al [10] and Gupa et al [11], the set of corresponding empirical time constants, T p , T f , T v , T vl , is as follows: 1.7, 8.0, 1.0, and 7.0, where T p and T f are related to the first-order lag of the leading-edge separation and trailing-edge separation, respectively, and both T v and T vl are the non-dimensional time constants related to the movement of the dynamic vortex.…”
Section: Unsteady Separated Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows an example of the force response of a pitching blade, simulated by the the LB model, and the features described above are present. Previous studies has shown that two iterations are sufficient to approach convergence for the LB model [11,24]. Therefore, the LB model runs two loops during each iteration of the DMS model.…”
Section: Leishman-beddoes Modelmentioning
confidence: 99%
“…An overview of the dynamic stall models adapted for the VAWTs applications can be found in [11,12]. The Gormont model [13], modified by Massé and Berg [14,15], is widely used for VAWTs simulations due to its simplicity of implementation [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%